Benchmarking Academic Anatomic Pathologists - Barbara S. Ducatman MD; Tristram Parslow MD, PhD (Elsevier, 2016)
The most common benchmarks for faculty productivity are derived from Medical Group Management Association (MGMA) or Vizient-AAMC Faculty Practice Solutions Center ® (FPSC) databases. The Association of Pathology Chairs has also collected similar survey data for several years. We examined the Association of Pathology Chairs annual faculty productivity data and compared it with MGMA and FPSC data to understand the value, inherent flaws, and limitations of benchmarking data. We hypothesized that the variability in calculated faculty productivity is due to the type of practice model and clinical effort allocation. Data from the Association of Pathology Chairs survey on 629 surgical pathologists and/or anatomic pathologists from 51 programs were analyzed. From review of service assignments, we were able to assign each pathologist to a specific practice model: general anatomic pathologists/surgical pathologists, 1 or more subspecialties, or a hybrid of the 2 models. There were statistically significant differences among academic ranks and practice types. When we analyzed our data using each organization's methods, the median results for the anatomic pathologists/surgical pathologists general practice model compared to MGMA and FPSC results for anatomic and/or surgical pathology were quite close. Both MGMA and FPSC data exclude a significant proportion of academic pathologists with clinical duties. We used the more inclusive FPSC definition of clinical "full-time faculty" (0.60 clinical full-time equivalent and above). The correlation between clinical full-time equivalent effort allocation, annual days on service, and annual work relative value unit productivity was poor. This study demonstrates that effort allocations are variable across academic departments of pathology and do not correlate well with either work relative value unit effort or reported days on service. Although the Association of Pathology Chairs-reported median work relative value unit productivity approximated MGMA and FPSC benchmark data, we conclude that more rigorous standardization of academic faculty effort assignment will be needed to improve the value of work relative value unit measurements of faculty productivity.